Reduced dopamine transporter availability in drug‐naive adult attention‐deficit/hyperactivity disorder - Shuntaro Itagaki; Takashi Ohnishi; Wataru Toda; Aya Sato; Junya Matsumoto; Hiroshi Ito; Shiro Ishii; Ryo Yamakuni; Itaru Miura; Hirooki Yabe (PCN Reports, 2024)
Abstract Aim This study aimed to clarify the abnormalities in dopamine transporter (DAT) availability in drug‐naive adult patients with attention‐deficit/hyperactivity disorder (ADHD) and the relationship between ADHD symptoms and abnormalities in DAT availability. Methods Single‐photon emission tomography (SPECT) was performed using iodine‐123‐β‐carbomethoxy‐3β‐(4‐iodophenyltropane) (I‐123 β CIT) as a tracer to measure in vivo DAT availability in 20 drug‐naive patients with ADHD [mean age ± standard deviation (SD)]: 25 ± 3.44 years; male:female = 11:9] and 20 age‐ and sex‐matched healthy controls (HCs) (mean age ± SD: 23.9 ± 2.27 years). Comparisons of DAT availability between HCs and adult patients with ADHD and the association between symptom severity and DAT availability within the ADHD group were analyzed using Statistical Parametric Mapping 12. Results Drug‐naive adults with ADHD showed significantly reduced DAT availability in the bilateral nucleus accumbens compared with HCs. Correlation analyses revealed a negative correlation between the severity of inattentive symptoms in adult patients with ADHD and DAT availability in the bilateral heads of the caudate nucleus, indicating the association between severe inattentive symptoms and lower DAT availability in the caudate nucleus. Conclusion In drug‐naive adult patients with ADHD, DAT availability was reduced in the nucleus accumbens, an important part of the reward system. This finding indicates the importance of the DAT in the reward system in the pathogenesis of ADHD. Inattentiveness was associated with DAT availability in the caudate nucleus, suggesting involvement of the cortico‐striato‐thalamo‐cortical circuit.